Periplasmic Bacterial Biomineralization of Copper Sulfide Nanoparticles - Yeseul Park; Zohar Eyal; Péter Pekker; Daniel M. Chevrier; Christopher T. Lefèvre; Pascal Arnoux; Jean Armengaud; Caroline L. Monteil; Assaf Gal; Mihály Pósfai; Damien Faivre (Advanced Science, 2022)
Abstract Metal sulfides are a common group of extracellular bacterial biominerals. However, only a few cases of intracellular biomineralization are reported in this group, mostly limited to greigite (Fe3S4) in magnetotactic bacteria. Here, a previously unknown periplasmic biomineralization of copper sulfide produced by the magnetotactic bacterium Desulfamplus magnetovallimortis strain BW‐1, a species known to mineralize greigite (Fe3S4) and magnetite (Fe3O4) in the cytoplasm is reported. BW‐1 produces hundreds of spherical nanoparticles, composed of 1–2 nm substructures of a poorly crystalline hexagonal copper sulfide structure that remains in a thermodynamically unstable state. The particles appear to be surrounded by an organic matrix as found from staining and electron microscopy inspection. Differential proteomics suggests that periplasmic proteins, such as a DegP‐like protein and a heavy metal‐binding protein, could be involved in this biomineralization process. The unexpected periplasmic formation of copper sulfide nanoparticles in BW‐1 reveals previously unknown possibilities for intracellular biomineralization that involves intriguing biological control and holds promise for biological metal recovery in times of copper shortage.